ChemInform Abstract: Facile Esterification of Alcohols with 2‐Acyl‐4, 5‐dichloropyridazin‐3(2H)‐ones under Friedel—Crafts Conditions. Issue 7 (29th January 2015) - Kim, Bo Ram; Sung, Gi Hyeon; Ryu, Ki Eun; Yoon, Hyo Jae; Lee, Sang‐Gyeong; Yoon, Yong‐Jin
Abstract The esterification method shows no chemoselectivity in the presence of amino and mercapto groups, but allows the selective acylation of aliphatic alcohols in the presence of aromatic alcohols.